2015
DOI: 10.3389/fnhum.2015.00457
|View full text |Cite
|
Sign up to set email alerts
|

Take your seats: leftward asymmetry in classroom seating choice

Abstract: Despite an overall body symmetry, human behavior is full of examples of asymmetry, from writing or gesturing to kissing and cradling. Prior research has revealed that theatre patrons show a bias towards sitting on the right side of a movie theatre. Two competing theories have attempted to explain this seating asymmetry: one posits that expectation of processing demand drives the bias; the other posits that basic motor asymmetries drive the bias. To test these theories we assessed the real-world classroom seati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…This prediction was not supported. Similar to the results of the Harms et al (2015) study, no differences in seating preferences were found between the left and the right side door entrances on any of the group differences investigated.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This prediction was not supported. Similar to the results of the Harms et al (2015) study, no differences in seating preferences were found between the left and the right side door entrances on any of the group differences investigated.…”
Section: Discussionsupporting
confidence: 86%
“…Research Question 3: Does the placement of the classroom door affect the seating preferences of college students in general or student veterans? Harms et al (2015) found that the entrance position did not affect student seating preferences, but that study was only investigating overall asymmetry in seating locations. However, Alschuler and Yarab (2018) described the experience of a student veteran who was constantly monitoring the environment for threats and planning escape.…”
Section: Research Questionmentioning
confidence: 93%
See 1 more Smart Citation
“…To account for it Nicholls et al postulated either a right turning bias (after Scharine & McBeath, 2002) or a feeling of proximity to the entrance (universally on the left in aircraft) as potential explanations. A leftwards bias has subsequently also been reported for classrooms (Harms, Poon, Smith & Elias, 2015), these authors interpreting the contrast with bias previously observed in cinemas (Harms, et al (2014) as an effect of "expectation bias", with expectation of emotional processing in cinemas biasing seat choice to the right, whilst expectation of verbal interaction in the classroom biasing choice to the left.…”
mentioning
confidence: 64%
“…Furthermore, couples and families who wish to travel together, personal preferences for aisle and window seats or front or rear seats, presence of exits, galleys, toilets and other asymmetries in layouts may well serve to complicate the choice process. Mild cognitive biases like pseudoneglect are unlikely to supersede such explicit preferences and hence may either be obscured or produce unexpected effects in observational ecological research like that of Nicholls et al (2013) and Harms et al (2014Harms et al ( , 2015.…”
mentioning
confidence: 99%